1977
DOI: 10.2508/chikusan.48.10_554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fibers on Liver Lipid Accumulation in Chicks

Abstract: Effect of dietary fibers such as cellulose, pectin and konjac mannan on lipid metabolism, especially on liver lipid accumulation, were investigated in three experiments on growing chicks. Each dietary fiber was supplemented at the level of 4 percent to a basal fiber-free diet or a semipurified diet containing 0.5 percent crude fiber, and the diets were fed for 54, 32, or 19 days from 14 day of age, respectively. Feeding of cellulose had no effect on the body weight gain, but feeding of pectin or mannan depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…() indicated that using 3% CEL resulted in a decrease in broiler breeders' abdominal fat and liver and plasma concentrations of cholesterol. Consistent with our findings, Akiba and Matsumoto () reported that plasma lipid concentration in chicks increased with force feeding, but that cellulose inclusion in the diet reduced this negative effect. In the current work, the inclusion of fibre in the diet did not affect the liver fatty acid concentration.…”
Section: Discussionsupporting
confidence: 93%
“…() indicated that using 3% CEL resulted in a decrease in broiler breeders' abdominal fat and liver and plasma concentrations of cholesterol. Consistent with our findings, Akiba and Matsumoto () reported that plasma lipid concentration in chicks increased with force feeding, but that cellulose inclusion in the diet reduced this negative effect. In the current work, the inclusion of fibre in the diet did not affect the liver fatty acid concentration.…”
Section: Discussionsupporting
confidence: 93%